2022
DOI: 10.3390/cancers14040952
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Open Dialogue about Complementary Alternative Medicine—A Phase II Randomized Controlled Trial

Abstract: Complementary alternative medicine (CAM) may reduce the symptom burden of side effects to antineoplastic treatment but also cause new side effects and non-adherence to conventional treatment. The aim of this RCT was to investigate the impact of open dialogue about complementary alternative medicine (OD-CAM) on cancer patients’ safety, health and quality of life (QoL). Patients undergoing antineoplastic treatment were randomly assigned to standard care (SC) plus OD-CAM or SC alone. The primary endpoint was freq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Recent publications demonstrate that systematically incorporating direct dialogue regarding CAM therapy into oncology clinic visits can improve patient experience without compromising patient safety or treatment efficacy. [28][29][30] Patients are not always comfortable disclosing CAM use with their physicians, as highlighted by our finding that approximately a quarter of patients do not tell their treating oncologist of their CAM use. A recent systematic review reported a 41% weighted disclosure rate of CAM use in North America, placing the rates of disclosure found in our study much higher.…”
Section: Discussionmentioning
confidence: 94%
“…Recent publications demonstrate that systematically incorporating direct dialogue regarding CAM therapy into oncology clinic visits can improve patient experience without compromising patient safety or treatment efficacy. [28][29][30] Patients are not always comfortable disclosing CAM use with their physicians, as highlighted by our finding that approximately a quarter of patients do not tell their treating oncologist of their CAM use. A recent systematic review reported a 41% weighted disclosure rate of CAM use in North America, placing the rates of disclosure found in our study much higher.…”
Section: Discussionmentioning
confidence: 94%
“…OD-CAM has been developed and described in our previous study (CAMONCO 1) 32. As in CAMOCO 1, patients in the intervention group will receive SC and participate in one or two sessions on OD-CAM facilitated by a nurse-specialist, who has completed the programme Fellowship in Integrative Medicine at The University of Arizona, USA.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The nurse-specialist does not offer CAM treatments. The guideline for OD-CAM is presented in table 1, and was developed in our previous study (CAMONCO 1) 32…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing interest of healthcare professionals in TCIM and the increasing number of scientifically validated studies, patients often turn to TCIM without professional input, taking information from unverifiable sources such as social networks, friends, and other patients, taking these products as self-medication [19][20][21], often underestimating the risks of adverse events, especially when taken in combination with chemotherapy (CT) [22][23][24][25]. Patients expect as main benefits a reduction of chemotherapy side effects, damage avoidance or minimization, boosting the immune system, and improvement of the response to conventional therapies [26,27].…”
Section: Introductionmentioning
confidence: 99%